Water resilience for human prosperity - Rockström, Johan; Falkenmark, M.; Folke, C.; Lannerstad, Mats; Barron, Jennie; Enfors, E.; Gordon, L.; Heinke, J.; Hoff, M.; Pahl-Wostl, Claudia (Cambridge University Press, 2014)
The world's human population now constitutes the largest driving force of changes to the biosphere. Emerging water challenges require new ideas for governance and management of water resources in the context of rapid global change. This book presents a new approach to water resources, addressing global sustainability and focusing on socio-ecological resilience to changes. Topics covered include the risks of unexpected change, human impacts and dependence on global water, the prospects for feeding the world's population by 2050, and a pathway for the future. The book's innovative and integrated approach links green and blue freshwater with terrestrial and aquatic ecosystem functions and use. It also links changes arising from land-use alteration with the impacts of those changes on social-ecological systems and ecosystem services. This is an important, state-of-the-art resource for academic researchers and water resource professionals, and a key reference for graduate students studying water resource governance and management. The book: - Contributes an important and novel perspective to the current paradigm of integrated water resource management - Provides a deeper understanding of the role of freshwater for ecosystem functions and services - Places water in relation to, and in interactions with, other key global change dynamics such as climate change and globalisation